Physiological and pharmacological aspects of the vas deferens—an update - Koslov, David S.; Andersson, Karl-Erik (Frontiers in Pharmacology, 2013)
The vas deferens, a muscular conduit conveying spermatozoa from the epididymis to the urethra, has been used as a model tissue for smooth muscle pharmacological and physiological advancements. Many drugs, notably α-adrenergic antagonists, have effects on contractility and thus normal ejaculation, incurring significant side effects for patients that may interfere with compliance. A more thorough understanding of the innervation and neurotransmitter pharmacology of the vas has indicated that this is a highly complex structure and a model for co-transmission at the synapse. Recent models have shown clinical scenarios that alter the vas contraction. This review covers structure, receptors, neurotransmitters, smooth muscle physiology, and clinical implications of the vas deferens.